Comparison of the Outcome of Electric Vacuum Aspiration and Conventional Dilatation and Curettage in First Trimester Miscarriages (Medical Forum Monthly, 2021)
Objective: To compare the outcome of electric vacuum aspiration and evacuation of retained products of conception in 1st trimester miscarriages.Study Design: Randomized Controlled Trial study.Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Shahida Islam Teaching Hospital Lodhran from January 2019 to December 2020.Materials and Methods: A total of 108patients with 1st trimester miscarriages, 18 to 40 years of age were included. Patients with signs of septic abortion, ectopic pregnancy, CRF, CLD and any bleeding disorders were excluded. Group ‘A’ patients underwent electric vacuum aspiration (EVA) while group ‘B’ patients underwent dilatation and curettage (DNC). Outcome variables like blood loss, hospital stay, uterine perforation and incomplete evacuation were noted.Results: The mean age of women in group A was 28.52 ± 4.76 years and in group B was 29.08 ± 5.83 years. Gestational age was from <12 weeks with mean gestational age of 6.93 ± 2.61 weeks. In this study, mean blood loss was seen in EVA as 68.72 ± 11.28 ml and 83.85 ± 8.94 ml in DNC with p-value of 0.0001. Also hospital stay was seen in EVA as 24.92 ± 3.62 hours and 38.23 ± 5.73 hours in DNC with p-value of 0.0001. Incomplete evacuation was found in DNC group as 00 (0.0%) and in MVA group as 02 (1.85%) with p-value of 0.155. The uterine perforation was seen in 06 (11.11%) patients of DNC group and 2 (3.70%) patients of EVA group with p-value of 0.038.Conclusion: This study concluded that electric vacuum aspiration (EVA) is effective and safe procedure as compared to conventional DNC in 1st trimester miscarriages.